Determinasi Total Aset Unit Usaha Syariah di Indonesia Tahun 2014-2019 - Shovia Indah Firdiyanti; Muchlis Muchlis; Arif Afendi (Business Management Journal, 2021)
The research aims to determine of the effect of Office Channeling, Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and BI Rate on the total assets of sharia business units in 2014-2019. The research approach used is a quantitative. The data used is data in the form of time series obtained from sharia banking statistics reports published by the Financial Services Authority and BI Rate from Indonesian Banks. The population in this study are all sharia business units in Indonesia. The sample used was 60 data from October 2014 to September 2019. This study used multiple regression analysis that was processed through the SPSS 16.0 program.The results of hypothesis testing show that partially office channeling has a positive and significants effect with a regression value of 91,444. FDR has a negative but not significants effect with a regression value of -224,687. NPF has a negatice and significants effect with a regression value of -11559,375. And the BI Rate has a positive and significants effect with a regression value of 9270,970. Of the four independent variables shows that the magnitude of the effect largest variable is NPF. Therefore the bank must maintain the quality of the NPF so as not to interfere.